The Dialectic of Sustainability Assurance and Greenwashing: The Illusion of Transparency? - Alkam, Rahayu; Dahlan, Lukman; Akbar, Wina Ayudia (Advances in Management & Financial Reporting, 2025)
Purpose: This study aims to examine the relationship between sustainability assurance and greenwashing practices, as well as to identify the extent to which assurance can strengthen accountability or instead become a means of symbolic legitimization that creates an illusion of transparency in sustainability reports. Research Method: This study employs a narrative review approach, compiling literature from various international and national journals relevant to the topics of sustainability reporting, assurance, and greenwashing. The selected literature is analyzed thematically through a process of categorization, interpretation, and synthesis to construct a comprehensive narrative. Results and Discussion: The results of the study show that although sustainability assurance has the potential to increase the credibility of sustainability reports, this practice is also vulnerable to being exploited by companies as an image-building strategy that glosses over greenwashing practices. Superficial or formalistic assurance often does not reflect operational realities, thereby causing distrust among stakeholders. Implications: This study emphasizes the need for assurance standards that are more rigorous, transparent, and adaptable to the local context. From a practical standpoint, the results of this study serve as a reflection for regulators, auditors, and companies to make assurance not just a symbol, but a real instrument in strengthening accountability.